Students’ mistakes in fulfilling the generic structure criteria of narrative text draft - Kurniawan, Agung Budi (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
Generic structure quality fulfilment of a narrative text draft gives benefits to be constructed as a qualified full paper. This research aims to reveal English college students’ mistakes in constructing proper narrative text generic structure drafts. The data is 45 students’ work. The students were ordered to construct a title and write a narrative draft that consisted of orientation, complications, and resolutions in the social problem area. The drafts were analyzed for linguistic fulfilment of those three parts of the generic structure. The finding of students’ mistakes in constructing the orientation draft proposed is unclear, and the subject’s identity is absent, as well as the absence of supporting information and the main problem statement. The students’ mistakes in constructing complications are proposing incoherent stories that are not related to orientation, jumbling stories, focusing on different figures with the orientation, giving over quantity of personal perspective, and the absence of conflict development. The students’ mistakes in constructing the resolution are writing only the conclusion and giving no solution. English teachers or lecturers are suggested to investigate and improve students’ linguistic backgrounds to be coherent with the narrative text before giving the writing training practice.